Safety of CT‐guided cervical nerve root corticosteroid injections. Issue 3 (12th March 2019) - Lukies, Matthew W; Teoh, Wesley WH; Clements, Warren
Abstract: Introduction: Computed tomography‐guided cervical nerve root corticosteroid injections are a commonly performed procedure for cervical radiculopathy. There have been major complications such as spinal cord infarction and posterior circulation stroke reported mostly with X‐ray fluoroscopic‐guided methods, however, there is relatively little data on the safety of newer CT‐guided methods. The purpose of this study was to identify any major complications and evaluate the rate of minor complications from CT‐guided cervical nerve root corticosteroid injections performed in a tertiary public hospital. Methods: Four hundred and three CT‐guided cervical nerve root injection procedures were identified over a period from July 2015 to January 2018 using the radiology information system (RIS) and data collected about the technique and any immediate complications. Patient follow‐up and delayed complications were then reviewed, either via outpatient clinic records or telephone consultation. Results: Two hundred and eighty‐six procedures were performed by radiology registrars or fellows, and 117 by radiologists, most commonly via an anterolateral approach and injecting 4 mg (in 1 mL) of dexamethasone. Follow‐up data were obtained for all 403 procedures and identified 16 minor complications, but no major neurovascular complications. Conclusion: The overall recorded rate of minor complications with CT‐guided nerve root injection was 4.0% with no major neurovascular complications, suggesting that CT‐guided transforaminal cervical corticosteroid injection is a safe procedure.